Reward-based service provisioning scheme for UAV-MEC assisted IoT infrastructures. (22nd June 2021) - Chowdhury, Mahfuzulhoq
To lower the IoT device task execution latency, unmanned aerial vehicles (UAVs) are gaining popularity among researchers that offers ubiquitous computing and communication services to IoT devices. To maximise the system task execution time and energy saving in different real-time cases, collaboration among UAV and mobile-edge computing (MEC) for IoT device task execution seems to be a promising solution. The existing task execution algorithm in the integrated UAV-MEC system suffers from higher latency and energy wastage due to lack of a proper IoT service provisioning scheme. To accomplish both time and energy gain, this paper presents a reward-based service provisioning scheme for UAV-MEC assisted IoT infrastructures by taking into account different types of UAV, IoT device, cloud, and task properties. Simulation results indicate that our proposed reward-based service provisioning algorithm outperforms the traditional air and ground offloading algorithm in terms of system timespan delay and energy cost latency.